Respostas
respondido por:
2
f(z) = z³
Sabemos que z = x+iy então:
f(z) = z³
f(x+iy) = (x+iy)³
f(x+iy) = x³ + 3 . x² . iy + 3 . x . (iy)² + (iy)³
f(x+iy) = x³ + 3 . x² . iy + 3 . x . i². y² + i³.y³
f(x+iy) = x³ + 3 . x² . iy + 3 . x . (-1). y² + (-i).y³
f(x+iy) = x³ + 3x²iy - 3xy² -iy³
f(x+iy) = x³- 3xy² + i(3x²y - y³)
u (x,y) = x³- 3xy²
v (x, y) = 3x²y - y³
Sabemos que z = x+iy então:
f(z) = z³
f(x+iy) = (x+iy)³
f(x+iy) = x³ + 3 . x² . iy + 3 . x . (iy)² + (iy)³
f(x+iy) = x³ + 3 . x² . iy + 3 . x . i². y² + i³.y³
f(x+iy) = x³ + 3 . x² . iy + 3 . x . (-1). y² + (-i).y³
f(x+iy) = x³ + 3x²iy - 3xy² -iy³
f(x+iy) = x³- 3xy² + i(3x²y - y³)
u (x,y) = x³- 3xy²
v (x, y) = 3x²y - y³
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás